Similar protective immunity induced by an inactivated enterovirus 71 (EV71) vaccine in neonatal rhesus macaques and children. Issue 46 (17th November 2015) - Zhang, Ying; Wang, Lichun; Liao, Yun; Liu, Longding; Ma, Kaili; Yang, Erxia; Wang, Jingjing; Che, Yanchun; Jiang, Li; Pu, Jing; Guo, Lei; Feng, Min; et al.
Highlights: An effective immune response was induced by an inactivated EV71 vaccine in children. An effective immune response was induced by an inactivated EV71 vaccine in macaques. Similar immune responses were induced by this vaccine in children and macaques. Macaque is a reliable model for the evaluation of EV71 candidate vaccine. Abstract: During the development of enterovirus 71 (EV71) inactivated vaccine for preventing human hand, foot and mouth diseases (HFMD) by EV71 infection, an effective animal model is presumed to be significant and necessary. Our previous study demonstrated that the vesicles in oral regions and limbs potentially associated with viremia, which are the typical manifestations of HFMD, and remarkable pathologic changes were identified in various tissues of neonatal rhesus macaque during EV71 infection. Although an immune response in terms of neutralizing antibody and T cell memory was observed in animals infected by the virus or stimulated by viral antigen, whether such a response could be considered as an indicator to justify the immune response in individuals vaccinated or infected in a pandemic needs to be investigated. Here, a comparative analysis of the neutralizing antibody response and IFN-γ-specific T cell response in vaccinated neonatal rhesus macaques and a human clinical trial with an EV71 inactivated vaccine was performed, and the results showed the identical tendency and increased level of neutralizing antibody and the IFN-γ-specific T cell response stimulated by the EV71 antigen peptide. Importantly, the clinical protective efficacy against virus infection by the elicited immune response in the immunized population compared with the placebo control and the up-modulated gene profile associated with immune activation were similar to those in infected macaques. Further safety verification of this vaccine in neonatal rhesus macaques and children confirmed the potential use of the macaque as a reliable model for the evaluation of an EV71 candidate vaccine.